Strategic corporate social responsibility - Lisa Planer-Friedrich; Marco Sahm (Bamberg University, Bamberg Economic Research Group (BERG), 2017)
We examine the strategic use of Corporate Social Responsibility (CSR) in imperfectly competitive markets. The level of CSR determines the weight a firm puts on consumer surplus in its objective function before it decides upon supply. First, we consider symmetric Cournot competition and show that the endogenous level of CSR is positive for any given number of firms. However, positive CSR levels imply smaller equilibrium profits. Second, we find that an incumbent monopolist can use CSR as an entry deterrent. Both results indicate that CSR may increase market concentration. Third, we consider heterogeneous firms and show that asymmetric costs imply asymmetric CSR levels.
Keywords: D42; D43; L12; L13; L21; L22; 330; Corporate Social Responsibility; Market Concentration; Cournot Competition; Entry Deterrence; Strategic Delegation; Evolutionary Stability